2016
DOI: 10.1186/s12859-016-1067-9
|View full text |Cite
|
Sign up to set email alerts
|

Parallel computation of genome-scale RNA secondary structure to detect structural constraints on human genome

Abstract: BackgroundRNA secondary structure around splice sites is known to assist normal splicing by promoting spliceosome recognition. However, analyzing the structural properties of entire intronic regions or pre-mRNA sequences has been difficult hitherto, owing to serious experimental and computational limitations, such as low read coverage and numerical problems.ResultsOur novel software, “ParasoR”, is designed to run on a computer cluster and enables the exact computation of various structural features of long RNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
28
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 59 publications
0
28
0
Order By: Relevance
“…4A) indicates that elements outside of 5′ exon or 5′SS also participate in defining the context for U1 snRNP binding. A previous genome-wide bioinformatic analysis of about 350,000 5′SS indicates that 5′SS are highly structured genome-wide (29). Furthermore, in the accompanying manuscript we observed that a βglobin pre-mRNA with hybridized 5′ exon with its 5′SS on a single-stranded segment (EH3+4+ED1+2 mutant of β-globin) is still unable to assemble spliceosome even though the 5′SS resemble the consensus sequence and considered strong.…”
Section: Discussionmentioning
confidence: 60%
“…4A) indicates that elements outside of 5′ exon or 5′SS also participate in defining the context for U1 snRNP binding. A previous genome-wide bioinformatic analysis of about 350,000 5′SS indicates that 5′SS are highly structured genome-wide (29). Furthermore, in the accompanying manuscript we observed that a βglobin pre-mRNA with hybridized 5′ exon with its 5′SS on a single-stranded segment (EH3+4+ED1+2 mutant of β-globin) is still unable to assemble spliceosome even though the 5′SS resemble the consensus sequence and considered strong.…”
Section: Discussionmentioning
confidence: 60%
“…The algorithms were implemented by the authors, except for parameter file reading, which is based on ParasoR's implementation. (11) E. Computation time. To demonstrate computational efficiency, the computation time of the proposed method using the S151 Rfam Dataset (20) was measured.…”
Section: Resultsmentioning
confidence: 99%
“…We introduced maximum-span constraint to RintW in order to reduce the computational costs. While Turner energy parameters have been determined by experiments using short RNA, the computational analysis tends to be unstable when RNA can form long range base-pairs (11). Our method lost little by excluding long range base-pairs.…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, even for the noisy genome-wide analysis of the PARS data, IDR-based classification was also successful in associating the reproducibility of read enrichment and the strength of stem probability obtained in silico (Kawaguchi and Kiryu, 2016) (shown in Supplementary Figure 8). Taken together, using reactIDR case and control read enrichment criteria, we were able to infer the accessibility of each nucleotide with higher precision than that possible when using a raw read count, by employing the data on the reproducibility and reference structure.…”
Section: Characteristics Of Idr-based Structure Classification With Omentioning
confidence: 97%
“…Many previous studies have succeeded in inferring possible secondary structures or accessibility from both experimental and computational perspectives (Puton et al, 2013). Due to the difficulties in the experimental determination of RNA secondary structure prior to the development of the next-generation sequencing, a number of computational methods was developed to predict the secondary structure from sequences or sequence alignment data (Zuker et al, 1989) These methods were shown to be highly accurate in the small RNA analyses, but the time and computer memory requirements remain too high to be applicable at genome-wide level (Bernhart et al, 2006;Kawaguchi and Kiryu, 2016).…”
Section: Introductionmentioning
confidence: 99%